The Tasks of The Scientific Worldview in The Content of The Teacher's General Education - Kasimova Gavhar Islamovna (Genius Publishing Group, 2024)
The article provides information about its main features in accordance with modern ideas about the system of lifelong education. It is also reported that continuing education leads to the need to focus on the constant development of a person with knowledge and skills, capable of making decisions and taking various actions.
Keywords: lifelong education; knowledge; skills